Midterm Follow-Up Of Tlif In Single-Level Lumbar Disc Degeneration - Abdul Satar; Samir Khan Kabir; Muhammad Zahid Khan; Muhammad Arif Khan; Waqar Khan; Mazhar Ali; Muhammad Anwaar Ul Haq (Gandhara University, 2024)
OBJECTIVES This study aims to evaluate the midterm clinical and radiological outcomes of TLIF in patients with single-level lumbar disc degeneration. The focus is on assessing the procedure's effectiveness in terms of pain relief, functional improvement, and any potential complications. METHODOLOGY A retrospective cohort study was conducted at Hayatabad Medical Complex, Peshawar involving 120 patients who underwent single-level TLIF for lumbar disc degeneration between 2018-2023. The patients with a diagnosis of single-level lumbar disc degeneration confirmed by MRI, failure of conservative treatment for at least 6 months, and who underwent TLIF during the study period were included in the study. Data were collected on preoperative and postoperative pain scores, Oswestry Disability Index (ODI), and radiological parameters. SPSS version 24 was used. RESULTS The mean follow-up period was 36 months (range 24-48 months). There was a statistically significant improvement in both pain scores (p < 0.001) and ODI scores (p < 0.001). Fusion rates were high, with 92% of patients achieving solid fusion by the final follow-up. Complications were observed in 15% of the cases, with adjacent segment disease being the most common. CONCLUSION TLIF provides significant pain relief and functional improvement in patients with single-level lumbar disc degeneration at midterm follow-up. The procedure demonstrates a high fusion rate with an acceptable complication profile, making it a reliable option for this patient population